Characteristics Apple Fruit Bar: Addition Green Tea, Moringa Leaves Tea and Bay Leaves Tea - Gandhi, Fadia Putri Mahatma; Rosida, Dedin Finatsiyatull; Wicaksono, Luqman Agung (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Because about 95% of polyphenols do not absorb in the small intestine and instead enter the large intestine, they can provide calming or anti-stress benefits. Therefore, we developed Fruit Bar products using phenol-rich food ingredients like green tea, dried moringa, and dried bay leaves. This study aims to determine the effect of adding different infusions and types of tea on the quality of Fruit bars. This study used a Completely Randomized Design (CRD) with two factors: the type of tea (green tea, moringa leaf tea, bay leaf tea) and the amount of infusion added (40%, 50%, 60%), and the results were analyzed using 5% ANOVA. The best result came from adding 60% green tea infusion, which led to a water content of 23.00%, a pH of 3.5, crude fiber of 0.93%, a polyphenol content of 25.83 mg GAE/g, and an antioxidant activity of 78%.Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production